2005
DOI: 10.1002/ejoc.200400669
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed H/D Exchange

Abstract: The scope and limitation of an iridium-catalysed H/D exchange reaction has been investigated. Our results suggest a general mechanism for specific labelling at aromatic and non-aromatic double bonds by D 2 O if an electron-donating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 16 publications
0
14
0
5
Order By: Relevance
“…[16] In the area of homogeneous catalysis, Fels et al showed that a,b-unsaturated carboxylic acid derivatives can undergo H/ D exchange reactions at the b-position with D 2 O in the presence of IrA C H T U N G T R E N N U N G (COD)A C H T U N G T R E N N U N G (acac) (2 mmol%, 90 8C), presumably through cyclometallated intermediates. [17] Matsubara et al demonstrated that cyclic olefins such as cyclohexene and cyclodecene can undergo H/D exchange with D 2 O under irradiation of microwaves in the presence of RuCl 2 A C H T U N G T R E N N U N G (PPh 3 ) 3 (5 mol%, 140 8C, 0.34 MPa).…”
Section: Introductionmentioning
confidence: 99%
“…[16] In the area of homogeneous catalysis, Fels et al showed that a,b-unsaturated carboxylic acid derivatives can undergo H/ D exchange reactions at the b-position with D 2 O in the presence of IrA C H T U N G T R E N N U N G (COD)A C H T U N G T R E N N U N G (acac) (2 mmol%, 90 8C), presumably through cyclometallated intermediates. [17] Matsubara et al demonstrated that cyclic olefins such as cyclohexene and cyclodecene can undergo H/D exchange with D 2 O under irradiation of microwaves in the presence of RuCl 2 A C H T U N G T R E N N U N G (PPh 3 ) 3 (5 mol%, 140 8C, 0.34 MPa).…”
Section: Introductionmentioning
confidence: 99%
“…Mioskowski's group reported that 1,5,7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) showed to be an isotope exchange catalyst in CDCl 3 at room temperature toward ketones and other acidic substrates 3e . Although other methods for deuteration of ketones are available, such as using the Pd/C‐H 2 ‐D 2 O system, other catalysts such as calcium vanadate apatite, antibody 38C2, cyclooctadieneiridium(I) acetylacetonate, Ir‐NHC complexes, and Pd/C utilizing NaBD 4 for catalyst activation were also used. Eames's group indicated that the regioselective C ‐deuteration of a series of related acyclic and exocyclic enolates derived from substituted aryl ketones .…”
Section: Introductionmentioning
confidence: 99%
“…High reactivity and possibility to tune catalytic system by choosing ligands and solvent enable deuteration of α,β‐unsaturated carbonyl. For example, crotonic and cinnamic acids undergo deuteration at β‐position to carboxyl group with quantitative yield …”
Section: Fundamentals For Mechanism Of the Isotopic Exchange Reactionmentioning
confidence: 99%